2009
DOI: 10.1038/onc.2009.274
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of chemoresistance mediated by miR-140 in human osteosarcoma and colon cancer cells

Abstract: In this study, our high throughput microRNA (miRNA) expression analysis revealed that the expression of miR-140 was associated with chemosensitivity in osteosarcoma tumor xenografts. Tumor cells ectopically transfected with miR-140 were more resistant to methotrexate (MTX) and 5-fluorouracil (5-FU). Overexpression of miR-140 inhibited cell proliferation in both osteosarcoma U-2 OS (wt-p53) and colon cancer HCT 116 (wt-p53) cell lines, but less so in osteosarcoma MG63 (mut-p53) and colon cancer HCT 116 (null-p5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
289
0
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 372 publications
(302 citation statements)
references
References 38 publications
9
289
0
4
Order By: Relevance
“…In two studies by Song et al (34,35), miR-140 and -215 were found to be overexpressed in drug-resistant colorectal cancer cell lines. On the basis of their findings, these miRNAs correlated with resistance to the anticancer drugs methotrexate, 5-fluorouacil, and tomudex.…”
Section: Micrornas As Biomarkers For Chemoresistancementioning
confidence: 99%
See 1 more Smart Citation
“…In two studies by Song et al (34,35), miR-140 and -215 were found to be overexpressed in drug-resistant colorectal cancer cell lines. On the basis of their findings, these miRNAs correlated with resistance to the anticancer drugs methotrexate, 5-fluorouacil, and tomudex.…”
Section: Micrornas As Biomarkers For Chemoresistancementioning
confidence: 99%
“…On the basis of their findings, these miRNAs correlated with resistance to the anticancer drugs methotrexate, 5-fluorouacil, and tomudex. In addition, an analysis of possible protein targets for these miRNAs pointed to HDAC4 and DHFR, respectively (34,35).…”
Section: Micrornas As Biomarkers For Chemoresistancementioning
confidence: 99%
“…A number of miRNAs, including miR-140 and miR-215, have been shown to regulate osteosarcoma chemoresistance. 45,46 Ectopic miR-215 protected osteosarcoma and colon cancer cell lines from methotrexate (MTX) and Tomudex, whereas miR-140 overexpression desensitized osteosarcoma cells to MTX and 5-fluorouracil. More recently, miRNA expression analysis of chemoresistant patient samples and cell lines revealed a miRNA signature consisting of miR-92a, -99b, -132, -193a-5p and -422a that was capable of predicting response to ifosfamide, whereas miR-33a reduced cisplatin-induced apoptosis.…”
Section: Mirna Expression Influences Growth and Progression Of Osteosmentioning
confidence: 99%
“…It has been reported that several miRNAs were misregulated in osteosarcoma tissues or cells, such as miR-34, miR-21, miR-140, miR-223 and miR-195 (He et al, 2009;Song et al, 2009;Wu et al, 2011;Mao et al, 2012;Li et al, 2012;Zhao et al, 2013). For instance, expression of miR-34s was decreased in tumor samples, and MiR-34 genes underwent minimal deletions and epigenetic inactivation in osteosarcomas ).…”
Section: Discussionmentioning
confidence: 99%